(untitled) (The Voz a Vos Bulletin, 2024)
In the academic program of Bachelor of Performing Arts; Acting and Contemporary Dance specialty (training of actors and dancers) of eight semesters, only two semesters are taught the subject Voice I and Voice II, the program of subject one, has the specific objectives: “You will manage your vocal expression through the creative interpretation of poetic texts, including bodywork in a consistent manner” and part of the thematic content states: “Creative interpretation (to be evaluated). Free verse: Analysis by ideas, Review of its sounds, Rhythm, Vocal exercises, The rest of the body in the poetic text; which implies a disadvantage for actors in training since they lack knowledge of Classical Baroque theater and its interpretation.